Obstetricians’ Views for Reasons Decision-Making for Cesarean Section in Iran - Sedigheh Hantoosh Zadeh; Mamak Shariat; Azam-Sadat Mousavi; Leyla Sahebi; Raheleh Moradi; Nahid Farrokhzad (Acta Medica Iranica)
By increasing trend of cesarean sections (c-section) has raised the rate of health implications after c-section analogously. This study aimed to identify the factors influencing the choice of cesarean birth from obstetrician' perspective. Present study was a descriptive-analytical cross-sectional study at three medical centers dependent on Tehran University of Medical Sciences in 2022. The questionnaire included parents' demographic and economic factors, parents 'previous experiences and insistence of relatives, environmental and facilities, cultural and religious, the doctor's personal opinion, and the mother's clinical and psychological factors. In general, 67 gynecologists participated in the study. The average (SD) age and work experience of doctors was 42.95 (7.68), and 11.49 (8.35) years respectively. The most determining factors in the choice of cesarean delivery from the doctor's point of view were the maternal clinical and psychological factors. Other important factors were the culture and personal beliefs of the parents. The factor of fear of litigation and court in case of birth problems and complications was one of the other essential factors in choosing cesarean delivery. In the current study, the age and experience of the specialist doctor showed a positive correlation with the personal opinion of the gynecologists. Obstetricians and gynecologists are the final decision makers in choosing the type of delivery. To select the correct method, there is a need for a specific protocol for choosing the kind of delivery, and providing a suitable platform to resolve legal concerns and lawsuits.